Kerjasama Antarsektor Dalam Program Pertanian Padi Organik Untuk Mewujudkan Pembangunan Berkelanjutan (Sustainable Development) (Studi di Desa Sukorejo Kecamatan Sambirejo Kabupaten Sragen) - Sadhana Sutisari (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2013)
Abstract: Sragen District has implemented the organic rice farm in Sukorejo Village, Sambirejo Sub-district as a follow up of â€œGo Organic 2010â€ that be a national agenda of Agriculture Ministry. The organic rice farm program has complex components to support sustainable development, so it needs cross sector partnership to fill it up. This research aims to know the cross sector partnership on the organic rice farm program in Sukorejo Village, Sambirejo Sub-district, Sragen District to achieve sustainable development. This research uses descriptive qualitative research. The commitment and communication become main factor to achieves the success of cross sector partnership. The cross sector partnership is consolidation of the relation among sector which has no hierarchy to combine different competency and resource to complete not being substitution of organic rice farm program. The cross sector partnership on organic rice farm program brings a result which is based on the principle of sustainable development. This partnership becomes a role model agricultural development in other areas. Keywords: Cross Sector Partnership, Sustainable Development, Organic Farming Abstrak: Kabupaten Sragen telah melakukan penerapan pertanian padi organik di desa Sukorejo Kecamatan Sambirejo sebagai tindak lanjut dari agenda nasional Kementerian Pertanian Go Organic 2010. Komponen yang kompleks dalam menerapkan program pertanian padi organik serta dapat mendukung pembangunan berkelanjutan, membutuhkan kerjasama antarsektor untuk dapat memenuhinya. Penelitian ini bertujuan untuk mengetahui kerjasama antarsektor dalam program pertanian padi organik di Desa Sukorejo Kecamatan Sambirejo Kabupaten Sragen untuk mewujudkanÂ pembangunan berkelanjutan. Penelitian ini menggunakan jenis penelitian deskriptif kualitatif. Dalam membangun kerjasama antarsektor ini komitmen dan komunikasi menjadi modal utama untuk mencapai keberhasilan. Kerjasama antarsektor merupakan peleburan hubungan antarsektor yang tidak terikat hubungan hierarki untuk menggabungkan kompetensi dan sumber daya yang berbeda yang berperan untuk saling melengkapi bukan sebagai pengganti dalam penerapan program pertanian padi organik. Dalam kerjasama antarsektor dalam program pertanian padi organik telah membawa hasil pembangunan yang didasarkan pada prinsip pembangunan berkelanjutan. Pola kerjasama antarsektor dalam program pertanian padi organik telah menjadi panutan pembangunan pertanian di daerah lain. Â Kata Kunci: Kerjasama Antarsektor, Pembangunan Berkelanjutan, Pertanian Organik